Study on Learning Strategies of English Language Based on Multimedia Computer-Aided - Li, Cui (Journal of physics. Conference series, 2020)
This paper introduces the problems and opportunities of English language learning in the period of high development of computer technology, and highlights the importance of English language ability. After comparing with the traditional English language ability learning, the author draws many advantages of multimedia computer aided English language learning, and draws relevant conclusions.